An approach on defining competency in evidence‐based dentistry. (6th March 2017) - Marshall, T. A.; Straub‐Morarend, C. L.; Guzman‐Armstrong, S.; McKernan, S. C.; Marchini, L.; Handoo, N. Q.; Cunningham, M. A.
Abstract: Introduction: Assessment of evidence‐based dentistry (EBD) knowledge and behaviour is hampered by lack of explicit competency criteria. This void impedes instructional design and assessment of student growth during the educational process. Methods: Knowledge and cognitive domains supporting educational objectives in a pre‐doctoral dental programme were identified for each level of the EBD five‐step process. We articulated educational objectives with behavioural expectations for each level of skill acquisition at each step of the EBD process. Outcome evaluation criteria identify students' progressive level of skill acquisition from novice to expert. Results: The educational objectives, type of knowledge, and nature of the cognitive process supporting these objectives are presented for each step of the EBD process. For example, educational objectives of the "Ask" step include (i) to construct a question from the patient presentation and knowledge limitations that addresses the clinical problem and (ii) to articulate the Problem, Intervention/Exposure, Comparison, Outcome (PICO) components. Achievement of these objectives requires both factual information regarding the PICO format and the cognitive process of understanding. Educational outcome criteria consistent with a competent clinician include clear articulation of the PICO with identifiable pieces that relate to the clinical situation. Discussion: Assessment strategies for progression towards EBD competency are limited due to the complexity associated with evaluating EBD knowledge and behaviours. To evaluate performance, the EBD academic community must define competency expectations for entry into unsupervised general dental practice. Conclusion: This framework offers measurable outcome evaluation criteria to initiate a conversation with academic peers regarding current gaps in EBD assessment.